Effects of cutting interval on yields and nutritive values of King Napier grass (Pennisetum purpureum cv. King grass) under irrigation supply - Wijitphan, Sumran; Lowilai, Pornchai (Asia-Pacific Journal of Science and Technology, 2017)
The objective of this experiment was to investigate the effects of cutting intervals on yields and nutritive values of King napier grass (Pennisetum purpureum cv. King grass) under splingler irrigation at Khon Kaen Animal Nutrition Research and Development Center. The experiment was designed as randomized complete block design with 4 replications. The treatments were 4 cutting intervals as 25, 35, 45 and 55 day. The result of this study showed that the total dry matter yields (TDMY) signi cantly increased (P < 0.01) with an increase in cutting intervals . The TDMY of King napier grass were 5,230.8, 9,252.0, 10,778.2 and 12,042.0 kg./rai/year for cutting intervals of 25, 35, 45 and 55 day, respectively. CP and DMD signi cantly decreased (P < 0.01) with an increase in cutting intervals while ADF and NDF were opposite (P < 0.01). Thus, the optimal cutting interval were at the range of 35 - 45 days. These could be obtained TDMY of 9252.0 - 10,778.2 kg./rai/year and the content of CP, ADF, NDF, Ash and DMD were 11.1 - 12.8, 41.7-43.2, 67.0 - 69.8 and 72.9 - 75.9 %, respectively.